Plasmodium falciparum resistance to sulfadoxine-pyrimethamine in Africa: a systematic analysis of national trends - Floriano Amimo; Anthony Magit; Jahit Sacarlal; Kenji Shibuya; Masahiro Hashizume (BMJ Global Health)
Introduction The rising burden of drug resistance is a major challenge to the global fight against malaria. We estimated national Plasmodium falciparum resistance to sulfadoxine-pyrimethamine (SP) across Africa, from 2000 to 2020.Methods We assembled molecular, clinical and endemicity data covering malaria-endemic African countries up to December 2018. Subsequently, we reconstructed georeferenced patient data, using pfdhps540E and pfdhps581G to measure mid-level and high-level SP resistance. Gaussian process regression was applied to model spatiotemporal standardised prevalence.Results In eastern Africa, mid-level SP resistance increased by 64.0% (95% uncertainty interval, 30.7%–69.8%) in Tanzania, 55.4% (31.3%–65.2%) in Sudan, 45.7% (16.8%–54.3%) in Mozambique, 29.7% (10.0%–45.2%) in Kenya and 8.7% (1.4%–36.8%) in Malawi from 2000 to 2010. This was followed by a steady decline of 76.0% (39.6%–92.6%) in Sudan, 65.7% (25.5%–85.6%) in Kenya and 17.4% (2.6%–37.5%) in Tanzania from 2010 to 2020. In central Africa, the levels increased by 28.9% (7.2%–62.5%) in Equatorial Guinea and 85.3% (54.0%–95.9%) in the Congo from 2000 to 2020, while in the other countries remained largely unchanged. In western Africa, the levels have remained low from 2000 to 2020, except for Nigeria, with a reduction of 14.4% (0.7%–67.5%) and Mali, with an increase of 7.0% (0.8%–25.6%). High-level SP resistance increased by 5.5% (1.0%–20.0%) in Malawi, 4.7% (0.5%–25.4%) in Kenya and 2.0% (0.1%–39.2%) in Tanzania, from 2000 to 2020.Conclusion Under the WHO protocols, SP is no longer effective for intermittent preventive treatment in pregnancy and infancy in most of eastern Africa and parts of central Africa. Strengthening health systems capacity to monitor drug resistance at subnational levels across the endemicity spectrum is critical to achieve the global target to end the epidemic.